Satellite tracking of livestock - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
high tech approach to livestock identification and tracking to protect cattle and manage grazing resources in Botswana and Kenya.